101 Chambers : Congress, State Legislatures, and the Future of Legislative Studies - Squire, Peverill (Book collections on Project MUSE., 2005)
"The book compares and contrasts Congress and the state legislatures on histories, fundamental structures, institutional and organizational characteristics, and members. By highlighting the vast array of organizational schemes and behavioral patterns evidenced in state legislatures, the authors demonstrate that the potential for the study of American legislatures, as opposed to the separate efforts of Congressional and state legislative scholars, is to great to leave unexplored."--BOOK JACKET. Title Summary field provided by Blackwell North America, Inc. All Rights Reserved.